The protective effects of Levilactobacillus brevis FZU0713 on lipid metabolism and intestinal microbiota in hyperlipidemic rats - Xiaoyun Fan; Qing Zhang; Weiling Guo; Qi Wu; Jinpeng Hu; Wenjian Cheng; Xucong Lü; Pingfan Rao; Li Ni; Youting Chen; Lijiao Chen (Food Science and Human Wellness)
Levilactobacillus brevis FZU0713, a potential probiotic previously isolated from the traditional brewing process of Hongqu rice wine, may have the beneficial effects on improving lipid metabolism. This study aimed to evaluate the in vivo protective effects and possible mechanism of L. brevis FZU0713 on the disturbance of lipid metabolism in hyperlipidemic rats fed a high-fat diet (HFD). Results showed that oral administration of L. brevis FZU0713 could significantly inhibit obesity, ameliorate the lipid metabolism disorder, including serum/liver biochemical parameters and hepatic oxidative stress in HFD-fed rats. Histopathological result also indicated that dietary intervention of L. brevis FZU0713 could reduce the accumulation of lipid droplets in liver induced by 8 weeks HFD feeding. Furthermore, L. brevis FZU0713 intervention significantly increased the fecal levels of short-chain fatty acids (SCFAs, including acetate, propionate, butyrate, isobutyrate, valerate and isovalerate) in HFD-fed rats, which may be closely related to the changes of intestinal microbial composition and metabolic function. Intestinal microbiota profiling by 16S rRNA gene sequencing revealed that L. brevis FZU0713 intervention significantly altered the relative abundance of Coprococcus, Butyricicoccus, Intestinimonas, Lachnospiraceae FCS020 group, Ruminococcaceae_NK4A214 group, Ruminococcaceae_UCG-005 and UCG-014 at genus levels. Based on Spearman's rank correlation coefficient, serum and liver lipid metabolism related biochemical parameters were positively correlated with genera Ruminococcus, Pediococcus and Lachnospiraceae, but negatively correlated with genera Pseudoflavonifractor, Butyricicoccus and Intestinimonas. Furthermore, liver metabolomics analysis demonstrated that L. brevis FZU0713 had a significant regulatory effect on the composition of liver metabolites in hyperlipidemic rats, especially the levels of some important biomarkers involved in the metabolic pathways of arachidonic acid metabolism, primary bile acid biosynthesis, amino sugar and nucleotide sugar metabolism, taurine and hypotaurine metabolism, biosynthesis of unsaturated fatty acid, fructose and mannose metabolism, tyrosine metabolism, etc. Additionally, oral administration of L. brevis FZU0713 significantly regulated the mRNA levels of liver genes (including Acat2, Acox1, Hmgcr, Cd36, Srebp-1c and Cyp7a1) involved in lipid metabolism and bile acid homeostasis. In conclusion, our findings provide the evidence that L. brevis FZU0713 has the potential to improve disturbance of lipid metabolism by regulating intestinal microflora and liver metabonomic profile. Therefore, L. brevis FZU0713 may be used as a potential probiotic strain to produce functional food to prevent hyperlipidemia.